Child theology : diverse methods and global perspectives - Bunge, Marcia J. (Marcia JoAnn), 1954- (Orbis Books, 2021)
"Theologians rethink and reinterpret theological doctrines and practices regarding the strengths and vulnerabilities of one of the world's most exploited and marginalized groups: children"--